Clinical and Physiological Variables in Patients with Post-COVID-19 Condition and Persistent Fatigue - Santos, Maércio [UNESP]; Dorna, Mariana [UNESP]; Franco, Estefânia [UNESP]; Geronutti, Jéssica [UNESP]; Brizola, Luís [UNESP]; Ishimoto, Letícia [UNESP]; Barros, Yasmin [UNESP]; Costa, Adriele [UNESP]; Breda, Carolina [UNESP]; Marin, Caroline [UNESP]; Suetake, Fernanda [UNESP]; Azevedo, Paula [UNESP]; et al. (MDPI, 2024)
Background/Objectives: Post-COVID-19 condition can manifest through various symptoms such as dyspnea, cognitive disturbances, and fatigue, with mechanisms related to these symptoms, particularly those related to fatigue, still requiring further clarification. Therefore, our aim was to assess the clinical and physiological variables in patients with post-COVID-19 condition and persistent fatigue. Methods: After one year post-COVID-19 infection, the patients underwent a comprehensive evaluation, including a complete blood count, a metabolic panel, complete spirometry, and assessments of dyspnea, quality of life, anxiety and depression, physical capacity, body composition, muscle strength, comorbidities, and medications. The participants were categorized into two groups: G1—fatigue and G2—non-fatigue. Results: Seventy-seven patients (53% female; 55 ± 11.8 years) were included, 37 in G1 and 40 in G2. As for clinical markers and symptoms of illness, in those with persistent fatigue symptoms, a greater sensation of dyspnea [BDI score: 7.5 (6–9) vs. 12 (9–12), p < 0.001; mMRC score: 1 (1–2) vs. 0 (0–1), p = 0.002], worse quality of life [SGRQ total score: 1404 (1007–1897) vs. 497 (274–985); p < 0.001], higher levels of anxiety [HADS-A score: 8 (5–9) vs. 3 (0.5–4); p < 0.001], and a reduction in peripheral and inspiratory muscle strength [handgrip strength: 34 (28–40) vs. 40 (30–46.5) kgf, p = 0.044; MIP: −81 ± 31 vs. −111 ± 33 mmHg, p < 0.001)] were observed. Conclusions: Those with persistent fatigue exhibited a greater sensation of dyspnea, higher levels of anxiety, reduced peripheral and inspiratory muscle strength, and a greater impairment of quality of life. The severity of fatigue was influenced by the worsening quality of life, heightened anxiety levels, and decreased peripheral muscle strength. Additionally, the worse quality of life was associated with a higher sensation of dyspnea, lower muscle strength, and reduced physical capacity.
Keywords: dyspnea; fatigue; muscle strength; post-acute COVID-19 syndrome; quality of life